Evaluation of an adhesive system bond strength to the surface of bleachedenamel with 10% carbamide peroxide with and without fluoride - Lugo Varillas, Jocelyn Graciela (2008)
The purpose of this study in vitro was to evaluate the tensille strength of adhesive system to the surface of bleached enamel with 10% carbamide peroxide with and without fluoride. We used nine healtly third molars, divided into three groups: Control (unbleached), group I (bleached with 10% Opalescence), group II (bleached with 10% Opalescence PF). Bleaching groups had a period of bleaching of 6 hours per day at 37°C, during 14 consecutive days; the teeth during this period were stored in artificial saliva. We waited 7 days to put a resin block (Filtek Z350,3M) of 5x5x3mm (w,l,h) on the buccal, palate or lingual surface of each tooth, previously we used 35% phosphoric acid (Scothbond, 3M) and an adhesive system (Single Bond 2, 3M). We used a diamond bioactive disc to make a horizontal and vertical cut to obtain the specimens, which were stored in distilled water. After 24 hours, the specimens were tested with the microtensile method at 0.5mm/min. Data were analyzed with ANOVA and post Tukey tests to determine significant differences between the experimental groups (p<0.05). The results were: Control group = 30.51±7.48 MPa, group I= 24.51±7.96 MPa, group II= 28.47± 5.89 MPa. The bond strength of adhesive system to the surface of bleached enamel with 10% carbamide peroxide with 0.11% fluoride ion is more significant than the surface of bleached enamel with 10% carbamide peroxide without fluoride. Under conditions of this study, we concluded that the addition of fluoride ion in the carbamide peroxide (Opalescence) preserves the bond strength in comparison with carbamide peroxide that does not contain fluoride in its composition (Opalescence PF), after a bleaching period.